3R Based Waste Management in Jakarta Higher Education Institutions: An Application of Environmental Education to Create Sustainable Campus - Hendrarso, Panji (Technium Social Sciences Journal, 2021)
Jakarta is a city that has a serious problem in terms of solid waste management. The Jakarta Environmental Agency records 7,000 tons of waste generated every day in this city. The solid waste is produced from settlements, offices, schools to campuses which are transported daily by 1,200 garbage trucks. Of that amount, around 1,900 to 2,000 tons are plastic waste. Higher educational institutions have a key role in this regard to develop a sustainable society. The concept of sustainability in campus can be propagated to students through the initiatives such 3R activities namely reduce, reuse and recycle. However, until now there are still a lot of universities have not given full attention to the environmental issues. Therefore, the environmental education has not been implemented well among the academic community. This study aims at answering the questions on what factors made the environmental education have not been implemented well in higher education institutions and what should universities do to create sustainable campus. In this research, a case study approach is employed to 3 universities and semi structured interviews were conducted to a total of 19 participants, consists of university students, university top management, lecturers, NGO activist to gain the information on the implementation of 3R based waste management policy. Interviews were also conducted with the cleaning service team in 3 universities to find out whether the students understood how to sort the waste to be disposed of. The research proved that environmental education is urgent to be applied in universities to create the sustainable campus. Further analysis indicated that universities which have applied the 3R programs show higher student achievement compared to those which do not implement the 3R programs.